Deskripsi Krakteristik Hasil Tes Intelegensi Stanford-Binet Form L-M (SB L-M) pada Siswa Retardasi Mental di Tingkat Sekolah Dasar - Adhyatma, Made Dharmawan Rama (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2024)
This research aims to describe the characteristics of each aspect of intelligence from The Stanford-Binet Form L-M Test (SB L-M), namely General Comprehension, Visual-Motor Ability, Arithmetic-Reason, Memory and Concept, Vocab and Verbal Fluency, dan Judgement and Reasoning in students with mentally retarded at Inclusion A Elementary School. It is Hoped that the results of this research can help schools to determine the cognitive baseline as a basis for Individual Educational Program (IEP) for mentally retarded students. This research uses descriptive quantitative where the SB L-M Test result data is processed in Binetgram. The subjects were all retarded mentally students at Inclusion A Elementary School. Data analysis was carried out by interpreting the comparison of CA and MA, percentile analysis of success, and analysis of the upper age limit for success in each aspect. The results showed that the research subjects were classified as mild and moderate mentally retarded. Limitation in abilty occur in all aspects, but the aspects of visual-motor ability and memory and concept are the aspects that stand out the most and have the potential to be optimized. Meanwhile, the weakest aspects are arithmetic-reason and vocab and verbal fluency. Integration of the analysis results for aech aspect with the assessment results for each subject is needed as a baseline for creating a IEP.